Clean Energy Policies and Just Transition for Coal Industry Workers - Indah Dwiprigitaningtias; Rival Pahrijal; Paramita Andiani (Westscience Press, 2026)
Indonesia’s transition toward clean energy represents an important legal and policy response to climate change, environmental degradation, and the pursuit of sustainable development. However, the gradual reduction of coal dependency also creates significant legal and socio-economic challenges for workers and communities whose livelihoods rely on the coal industry. This study aims to examine the adequacy of Indonesia’s legal framework in ensuring a just transition for coal industry workers during the implementation of clean energy policies. The research employs a normative legal method using statutory, conceptual, comparative, and analytical approaches. Primary legal materials consist of constitutional provisions, national legislation, presidential regulations, and international legal instruments related to energy transition, environmental protection, labor rights, and social security. Secondary legal materials include academic journals, books, policy reports, and legal commentaries concerning clean energy governance and just transition. The findings indicate that Indonesia has established a relatively comprehensive legal framework supporting renewable energy development and greenhouse gas emission reduction. Nevertheless, the legal framework governing worker protection during the energy transition remains fragmented and insufficiently integrated. Existing regulations primarily emphasize environmental objectives and renewable energy investment while providing only general labor protection without specifically regulating workforce reskilling, employment transition, income protection, regional economic diversification, and institutional coordination. Consequently, legal uncertainty persists regarding the protection of coal industry workers affected by decarbonization policies. The study concludes that Indonesia requires a more comprehensive and integrated legal framework that harmonizes environmental sustainability with labor rights and social justice. Strengthening legislation concerning just transition, workforce protection, social dialogue, dedicated transition financing, and intergovernmental coordination is essential to ensure that Indonesia’s clean energy transition is equitable, inclusive, and capable of supporting long-term sustainable development.